Micro-seismic observations in Leeu Gamka, Karoo, South Africa - Fynn, Melody (Department of Geological Sciences, 2019)
This thesis documents a microseismicity study in the interior of South Africa. The study area is centred on Leeu Gamka in the Western Cape province, a tectonically stable intraplate setting and is therefore expected to be seismically quiet. The International Seismological Centre (ISC) catalogue reported localised anomalous seismicity in the region between 2007 and 2013 with local magnitudes up to 4.5. The short apparent duration and time history of this anomalous reported seismicity is likely a reporting artefact. An array of 23 geophones was deployed for three months (March - June) in 2015, covering an area of 60 km - 65 km centred on the zone of anomalous seismicity. Using this array, I identified a total of 106 earthquakes over this period, with almost all events clustering in a surprisingly small area (75% of the epicentres fall within a one square kilometre block). Double-difference relocation resolved the hypocentres onto a structure with an apparent NW - SE orientation, consistent with large-scale fabric that can be recognised in satellite imagery. The focal mechanisms display strike-slip faulting with the fault plane likely in a NW - SE orientation, consistent with the distribution of the earthquakes. The velocity model was tested by varying the thickness of the Karoo supergroup to investigate the sensitivity of the depths of the earthquakes. An average hypocentral depth of approximately 6 km was calculated for the earthquakes, assuming a depth to the base of the Karoo of 5km. This places the earthquakes just below the base of the Karoo in the Cape Supergroup. The magnitudes of the earthquakes recorded range from -1.5<ML<0.4, with a magnitude of completeness of -0.8, and follow a Gutenberg-Richter distribution with the b-value range of 1.23 - 2.07 calculated within a 90 % confidence range. The presence of such a structure has implications for shale gas exploration in that wastewater pumping in an area with active faulting could trigger larger and more frequent earthquakes, as seen in case studies in the central states of America, in particular, Oklahoma.